The influence of absorbing aerosols on the morning PBL growth dynamic in the EDMF-AERO modeling framework - G. M. Florczyk; K. M. Markowicz (Advances in Science and Research)
Using the novel PBL evolution model EDMF-AERO and the dataset collected during a measurement campaign at the Swider Geophysical Observatory in 2014, we studied morning PBL dynamics under high pollution. We tuned the model to the data and reached good accuracy in PBLH estimation (3 % deviation) and sufficient accuracy in the average potential temperature of PBL <mover accent="true">θPBL‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="6fbb2b50987970551a8a20894a212ad5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="asr-22-13-2025-ie00001.svg" width="24pt" height="15pt" src="asr-22-13-2025-ie00001.png"/></svg:svg> estimation (RMSE=2.7 K). The study focused on the Aerosol-PBL Interactions (API). In particular, we examined the influence of absorbing aerosol on the morning dynamics of PBL growth. Although no significant change in the height of the developed PBL was found, a nonzero convection onset delay was detected alongside the rapid formation of thermals. We also evaluated which one of the API component effects (“Surface cooling” or “Aerosol heating”) is dominant in terms of influence on <mover accent="true">θPBL‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="0f0edd265f5c62de31572ff24d92ea5f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="asr-22-13-2025-ie00002.svg" width="24pt" height="15pt" src="asr-22-13-2025-ie00002.png"/></svg:svg> and PBLH. The “Aerosol heating” component impacts <mover accent="true">θPBL‾</mover><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="7381505825964807a7953152bb963067"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="asr-22-13-2025-ie00003.svg" width="24pt" height="15pt" src="asr-22-13-2025-ie00003.png"/></svg:svg> variability around two times stronger than the “Surface cooling” component. In terms of PBLH, the two components are approximately equal in strength and cancel each other out, yielding no change in PBLH under heavy pollution compared to the clear-sky case.